MEMBANGUN KARAKTER BANGSA MELALUI PENGETAHUAN BAHASA, BUDAYA DAN PENERJEMAHAN - Wuryantoro, Aris (Prosiding PESAT, 2015)
This paper is intended to analyze the role of language, culture, and translation knowledge in strengthening the nation character. This research uses descriptive qualitative method by using content analysis. It reveals that language, culture, and translation knowledge can strengthen the nation character of Indonesia. Indonesian is a creative nation which is reflected from its language and culture creativities. Besides Indonesian’s cultures have been adopted by many other countries.